Pharmacophore Modelling-Based Drug Repurposing Approaches for SARS-CoV-2 Therapeutics - Rampogu, Shailima; Lee, Keun Woo (Frontiers in Chemistry, 2021)
The recent outbreak, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has caused a devastating effect globally with no effective treatment. The swift strategy to find effective treatment against coronavirus disease 2019 (COVID-19), is to repurpose the approved drugs. In this pursuit an exhaustive computational methods have been used on the DrugBank compounds targeting nsp16/nsp10 complex (PDB code: 6W4H). A structure-based pharmacophore model was generated and the selected model was escalated to screen DrugBank database, resulting in five compounds. These compounds were subjected to molecular docking studies at the proteins binding pocket employing the CDOCKER module available with the Discovery Studio v18. In order to discover potential candidate compounds, the cocrystallized compound S-adenosyl methionine (SAM) was used as the reference compound. Additionally, the compounds Remdesivir and Hydroxychloroquine were employed for comparative docking. The results have shown that four compounds have demonstrated a higher dock score than the reference compounds and they were upgraded to molecular dynamics simulation (MDS) studies. The MDS results have yielded three compounds, Framycetin, Kanamycin and Tobramycin as promising candidate compounds. They have represented a stable binding mode at the targets binding pocket with an average protein backbone RMSD below 0.3 nm. Additionally, they have prompted the hydrogen bonds during the entire simulations inferring that the compounds have occupied the active site firmly. Taken together, our findings propose Framycetin, Kanamycin and Tobramycin as potent putative inhibitors for COVID-19 therapeutics.